Influence of tank mixtures herbicides in pre-emergence of the chia crop (Research, Society and Development, 2020)
The benefits of chia in human food have been widely explored because its seeds are rich in omega 3, minerals, fibers and proteins. However, crop management information is still restricted, such as the proper use of herbicides for weed control. This research aimed to evaluate the herbicides combinations efficiency and selectivity applied in Salvia hispanica pre-emergence. The experiment was developed in the field, Guarapuava, Paraná State, using a randomized block design, with thirteen treatments and four replications. The treatments were represented by isolated and/or associated herbicides in the respective doses (g ha-1): trifluralin (1440); linuron (990), sulfentrazone (100; 200 and 300), linuron + trifluralin (247+1440; 495+1440 and 990+1440), sulfentrazone + trifluralin (100+1440; 200+1440 and 300+1440), as well as non-applied control and another weeded throughout the whole crop cycle. The tank mixtures with sulfentrazone + trifuralin caused low intoxication to chia culture and the best levels of weed control, being the 100 + 1440 g ha-1 dose the safest one in relation to development and productivity of grains. Sulfentrazone + trifluralin (100 + 1440 g ha-1) and linuron + trifluralin (247 + 1440 g ha-1) were the most selective associations to chia crop. The isolated application of sulfentrazone, trifluralin and linuron was not feasible for the weeds mixed infestation management in the chia crop.